Does Perceived Stress of University Students Affected by Preferences for Movie Genres? an Exploratory Cross-Sectional Study in China - Qiao, Ning (Frontiers in Psychology, 2021)
This study aims to explore whether different preferences for movie genres were related to different perceived stress of college students. An online questionnaire was designed and students filled out by the 1549 students voluntarily. The 10-item perceived stress scale (PSS-10) and multinomial logistic regression were used to access the perceived stress and the association between the movie preference genres. Over 90% of participants had moderate to high levels of stress. Differences were found between participants with different stress perception states in terms of smoking history, active exercise, and sleep duration(p<0.05). Participants who showed a preference for suspense films were more probably have a lower stress (RRR1=0.34, RRR2=0.26, p<0.05). Additionally, students who preference for crime film and disaster film were more probably to have a higher stress (RRR=2.03, p<0.05, RRR=3.15, p<0.05)). And the significant gender gap in different film genres preferences was observed in our study (p<0.05). The male who showed the preference for horror films might be more probably to have a moderate stress (OR=3.68, p<0.05). And females who showed a preference for disaster were more probably to have a high stress (OR=3.27, p<0.05). One year and a half after the COVID-19 pandemic, the perceived stress of Chinese university students is high. The personal preferences for certain film genres were significantly associated with perceived stress. As for different film genre preferences, the preference for disaster, crime, and horror, being associated with high perceived stress, it may turn out to be useful to pay more attention to an individual’s film consumption. And suspense films could be used in mental health education interventions for college students to some extent in the future.